A systematic study on bio-inspired frameworks for fertilizer optimization - Amudha, T.; Amudha, T.; Thilagavathi, N.; Sangeetha, A. (International Journal of Agricultural Technology, 2021)
Fertilizers supply nutrients to the soil to intensify soil fertility and improve plant growth. Fertilizer application to the crops was optimized by identifying the optimal fertilizer requirement as per the soil type and encouraging the usage of manure. Complex fertilizers contain multiple nutrients in each individual granule. They are cost-effective as well as highly available, when compared to manure, but they always lead to imbalance of nutrients, either in excess or in shortage. Excessive usage of chemical nutrients affects the soil quality and also affects the ecology. To avoid the imbalance in nutrients, manure application is suggested in this work along with fertilizers. The research finding in fertilizer optimization is performed by using two well-known optimization algorithms, Fruit Fly Optimization (FFO) algorithm and Social Spider Algorithm (SSA) inspired from the biological species, fruit fly and spider. Agricultural region in Coimbatore district, situated in the state of Tamil Nadu, India Results found that excess application of fertilizer brought down with systematic optimization plans, through the harmful influences of fertilizers can be avoided to a greater extent